Cirrus Horizontal Heterogeneity and 3‐D Radiative Effects on Cloud Optical Property Retrievals From MODIS Near to Thermal Infrared Channels as a Function of Spatial Resolution. Issue 19 (8th October 2018) - Fauchez, T.; Platnick, S.; Sourdeval, O.; Wang, C.; Meyer, K.; Cornet, C.; Szczap, F.
Abstract: To retrieve cloud optical properties, current satellite operational imager algorithms simplify the forward radiative transfer problem by assuming that cloudy pixels are horizontally homogeneous and radiatively independent. This study investigates the effects of cirrus horizontal heterogeneity and 3‐D radiative effects on cloud optical thickness (COT) and ice crystal effective radius (CER) retrievals obtained using simulated nadir near‐infrared/shortwave‐infrared (NIR/SWIR) reflectances at 0.86 and 2.13 μm and thermal infrared (TIR) radiances at 8.5, 11.0, and 12.0 μm, first separately and next using the five wavelengths together. Synthetic cirrus radiation fields are generated using a cirrus 3‐D cloud generator and a 3‐D radiative transfer code. When both cloud 3‐D and heterogeneity effects are considered, the solar reflectance‐based retrievals have the largest errors (up to 10% for COT and 80% for CER, depending on solar angles) for spatial resolutions less than 500–1, 000 m, while the TIR‐based retrievals have the largest errors (up to 30% for COT and 50% for CER) above this resolution due to parallel homogeneous approximation bias. Therefore, TIR radiance‐based retrievals are preferable for spatial resolutions equal or higher than ~500 m to 1 km, while NIR/SWIR reflectance‐based retrievals are preferable for coarser spatial resolutions. The combination of NIR/SWIR and TIR measurements performed better together than individually for CER retrieval only for resolutions coarser than 2.5 km because 3‐D effects are negligible at this scale. Thus, the spectral dependence of subpixel cloud horizontal heterogeneity and 3‐D radiative effects has strong consequences when simultaneously using different channels for retrieving cirrus properties. Key Points: Below ~1‐km horizontal spatial resolution, NIR/SWIR reflectance‐based retrievals have the largest retrieval errors due to 3‐D radiative effect Above ~1‐km spatial resolution, TIR radiance‐based retrievals have the largest retrieval errors due to cloud horizontal heterogeneity Cloud optical retrievals from multispectral measurements can be severely impacted by the wavelength dependency of cloud heterogeneities and 3‐D radiative effects